Mechanical stratigraphy and structural control of oil accumulations in fractured carbonates of the Irati Formation, Parana Basin, Brazil - Cerri, Rodrigo Irineu [UNESP]; Luvizotto, George Luiz [UNESP]; Wohnrath Tognoli, Francisco Manoel; Warren, Lucas Verissimo [UNESP]; Okubo, Juliana [UNESP]; Morales, Norberto [UNESP] (Soc Brasileira Geologia, 2020)
Fracturing analysis of low-permeability rocks as reservoir analogs have increased in recent years. The main mechanism involved in the development of secondary porosity in low-permeability, fine-grained limestones of the Irati Formation is fracturing. In these rocks, oil accumulates along fracture planes, vuggy porosity, microfractures, breccias, as well as bedding discontinuities. Joints represent the central element for oil migration and the connection between accumulation sites. Joints are unevenly distributed across the succession of rock types, where carbonate rocks have a much denser array of joints than shales and siltstones. From a mechanical stratigraphy point of view, limestones have a brittle behavior and constitute mechanical units. Ductile shale and siltstone are mechanical interfaces capable of blocking joint propagation. Joints running NW-SE are more effective in trespassing the mechanical interface and are, therefore, more persistent. Joints running NE-SW are less persistent because the ductile behavior of the first two shale beds above the limestone blocks their propagation. The spatial arrangement of regional NW-SE and NE-SW joints promoted reservoir connection, allowing oil migration and accumulation. The joints and oil migration (at least three phases) developed as a consequence of the Gondwana Breakup and are also associated with local pressure gradients.
Keywords: mechanical stratigraphy; planar surfaces; fracture connection; Pitanga Structural High